2020
DOI: 10.1038/s41598-020-74869-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and enrichment of melanocytes from human corneal limbus using CD117 (c-Kit) as selection marker

Abstract: Limbal melanocytes (LM) are located in the basal epithelial layer of the corneoscleral limbus and interact with adjacent limbal epithelial progenitor cells. The exploration of their biological role in the maintenance of the limbal stem cell niche has been limited by the difficulty of LM isolation and cultivation. Here, we report on a facile protocol for the efficient isolation and enrichment of pure populations of human LMs by fluorescence-activated cell sorting (FACS) using antibodies raised against the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Earlier studies have shown that clusters derived from collagenase digestion included more epithelial progenitor cells, LMSCs, and melanocytes than dispase-isolated cell sheets [ 3 , 15 ]. Moreover, it has also been reported that cluster-derived cell suspensions contained more CD117 + /Melan-A + cells [ 24 ] and that stromal cells located immediately subjacent to limbal basal epithelial cells support LEPC better than stromal cells located in deeper stromal layers [ 18 , 19 ]. Hence, in the present study, we used the cluster-derived cells for efficient individual cell type-specific isolation of LEPC, LM and LMSC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies have shown that clusters derived from collagenase digestion included more epithelial progenitor cells, LMSCs, and melanocytes than dispase-isolated cell sheets [ 3 , 15 ]. Moreover, it has also been reported that cluster-derived cell suspensions contained more CD117 + /Melan-A + cells [ 24 ] and that stromal cells located immediately subjacent to limbal basal epithelial cells support LEPC better than stromal cells located in deeper stromal layers [ 18 , 19 ]. Hence, in the present study, we used the cluster-derived cells for efficient individual cell type-specific isolation of LEPC, LM and LMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported on a novel protocol to obtain LM in a very short period of time and to avoid any toxic effects exerted by commonly used selection agents [ 24 ]. However, the sorted CD117 + LM populations still contained small amounts of contaminating stromal cells in most of the cultures (6/7 cultures) and required a second CD117-based FACS sort [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations